Motivation and flow state in Brazilian under 23 basketball athletes - Guandalini Gasparin, Vanessa (2024)
OBJECTIVE: .The objective of the study was to present the motivation and flow state in Brazilian under 23 basketball athletes depending on sociodemographic characteristics. METHODS: The study was conducted through questionnaires carried out with basketball athletes during the Brazilian Interclub Under 23 Championship in 2022 in São José dos Pinhais - PR. Athletes identification forms, SMS-II (Sport Motivation Scale) and FSS-2 (Flow State Scale) questionnaires were used. To check the normality of the data, the Shapiro-Wilk test was used. The sample consisted of 75 female athletes with age of 20.8±2.20 years, who trained on average 13.4±5.47 hours per week, and were 9.82±3.05 years old. experience in the modality.RESULTS: The results demonstrated that the athletes perceive themselves to be intrinsically motivated, positively identifying themselves among the motivation regulations, Intrinsic Regulation (Md=6.00), Integrated Regulation (Md=6.00) and Identified Regulation (Md=5.67). In relation to the Flow State, it was identified that the athletes had higher medians in clear goals (Md=4.00), intense concentration (Md=4.00) and autotelic experience (Md=4.33).CONCLUSION: It is therefore concluded that basketball in brasilian context under 23, the athletes showed intrinsic motivation and a state of flow when practicing basketball.